2006
DOI: 10.1007/s10620-006-9128-y
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Adenosine Triphosphate and Adenosine Stimulate Proximal Sphincter of Oddi Motility Via Neural Mechanisms in the Anesthetized Australian Possum

Abstract: We aimed to determine if exogenous adenosine triphosphate or adenosine modulated sphincter of Oddi motility and involved neural mechanisms. Sphincter of Oddi motility was recorded in anesthetized possums by manometry. Adenosine triphosphate or adenosine (1 microM-10 mM) was applied topically to the sphincter before and after pretreatment with tetrodotoxin, hexamethonium, atropine, or Nomega-nitro-L-arginine methyl ester. Sphincter contraction amplitude and frequency were quantified. Adenosine triphosphate indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…ATPinduced muscularis mucosae contraction evokes epithelial secretion in rabbit distal colon via NANC secretomotor nerve stimulation and prostaglandin synthesis [550]. ATP is released as a neurotransmitter to stimulate mucosal secretion of electrolytes and H 2 O via P2Y 1 receptors expressed by VIPergic secretomotor nerves [213,712]. ATP is released by mechanical deformation from enterochromaffin cells to act as an autocrine or paracrine messenger to stimulate release of 5-HT from enterochromaffin cells via P2Y 1 receptors or on P2X3 receptors on sensory nerve subepithelial nerve terminals [726].…”
Section: Intestinal Secretionmentioning
confidence: 99%
“…ATPinduced muscularis mucosae contraction evokes epithelial secretion in rabbit distal colon via NANC secretomotor nerve stimulation and prostaglandin synthesis [550]. ATP is released as a neurotransmitter to stimulate mucosal secretion of electrolytes and H 2 O via P2Y 1 receptors expressed by VIPergic secretomotor nerves [213,712]. ATP is released by mechanical deformation from enterochromaffin cells to act as an autocrine or paracrine messenger to stimulate release of 5-HT from enterochromaffin cells via P2Y 1 receptors or on P2X3 receptors on sensory nerve subepithelial nerve terminals [726].…”
Section: Intestinal Secretionmentioning
confidence: 99%
“…Some studies report that only 14% of unknown abdominal pain after cholecystectomy could be ascribed to SOD 14 It has been reported that NO, as one of the most important neurotransmitters of non-adrenergic-non-cholinergic neurone (NANC) 15,16 , can inhibit the motion of SO 17,18 and induce FIGURE 5 -Effect of L-NAME and combining with physiological dose of CCK on SO motility after cholecystectomy: when L-NAME seemed to lose the excitatory effect after operation, the addition of CCK (20ng/ kg) inconceivably increased the motion of SO at least in ten minutes after injection.…”
Section: Effect Of Physiological Dose Of Cck (20ng/kg)mentioning
confidence: 99%
“…ATP and ADP were earlier shown to have inhibitory actions on the cat sphincter of Oddi (Persson 1976). In the Australian possum, ATP and adenosine increase motility in the sphincter of Oddi via cholinergic motor nerves, but can also decrease sphincter motility via a nitrergic pathway (Woods et al 2006). The excitatory response to ATP seems likely to involve P2X receptors, whereas the later inhibitory response is likely to involve P2Y receptors (Woods et al 2007).…”
Section: Pyloric Sphinctermentioning
confidence: 99%
“…Experiments carried out by Cuthbert and Hickman (1985) confirmed the earlier reports about the effects of ATP on transepithelial ion transport but, since they found that TTX virtually abolished the effects of ATP on electrogenic chloride secretion, they suggested that the effects of ATP were indirect, via neural elements in the intramural plexus. ATP is released as a neurotransmitter to stimulate mucosal secretion of electrolytes and H 2 O via P2Y 1 receptors expressed by VIPergic secretomotor nerves (Fang et al 2006;Woods et al 2006). Intrinsic enteric sensory neurons also provide direct innervation of the mucosa and stroking the mucosal lining of the guinea pig colon with a brush releases ATP that activates P2Y 1 , P2Y 2 and P2Y 4 receptors to trigger an intestinal neural reflex and an increase in shortcircuit current, indicative of chloride secretion (Christofi et al 2004;Ghanem et al 2005).…”
Section: Gutmentioning
confidence: 99%